Optimization of soybean distribution costs with the transportation method: a case in SME’s - Chairat, Arief Suardi Nur; Caswito, Ade; Octavia, Lia Nur; Asnul, Nur Shania; Fauziah, Annisa; Bahasoan, Alisya Sulifianti (Universitas Mercu Buana, 2024)
The distribution of soybean raw materials is not only related to aspects of quality and smooth production of tofu making but can also influence cost efficiency to increase competitiveness. In this situation, the number of soybeans shipped, transportation costs per unit, and the choice of transportation service used are transportation model issues. This research aims to determine the cheapest cost of sending soybean raw materials from four agent locations to three tofu factory locations with a choice of two transportation services that can be adopted. The case studied is a case of unbalanced transportation with supply greater than demand. The method used is the application of a transportation model, with the Northwest Corner method to determine the initial base solution and the Modified Distribution method to optimize distribution costs for soybean raw materials in the context of tofu production supply. Based on data processing, the results showed that the first and second transportation services offered services with a total shipping cost of IDR 691,750 and IDR 605,250. Observation of these differences leads to the conclusion that the second transportation service offers the most optimal value for money. The research results provide additional knowledge for tofu makers in optimizing costs and delivery routes for soybean raw materials, supporting production continuity, and increasing competitiveness in an ever-changing market.